Systems Biology of Parkinson's Disease - Wellstead, Peter; Cloutier, Mathieu; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
This text is the first to present a study of Parkinson$1 (Bs disease from a Systems Biology perspective. By placing the condition at centre stage, the authors have been able to provide a wide ranging modelling and systems analysis that is focussed on a multi-facetted and highly complex condition. The book comprises a specially selected set of eight studies of important aspects of PD, covering all relevant scales of space and time. These are used to show how innovative sensing techniques, mathematical modelling, model analysis and computational simulation can throw new light on the dynamics of disease mechanisms that drive this important form of neurodegeneration.s
Imaging of dopaminergic neurons and the implications for Parkinson$1 (Bs disease -- Modelling and simulation of brain energy metabolism: energy and Parkinson's disease -- Systems Biology of Aging: Opportunities for Parkinson$1 (Bs Disease -- Mitochondrion- and Endoplasmic Reticulum-Induced SK Channel Dysregulation as a Potential Origin of the Selective Neurodegeneration in Parkinson$1 (Bs Disease -- Energetics of Ion Transport in Dopaminergic Substantia nigra Neurons: ion exchange dynamics at the pacemaking membrane -- Real-time In Vivo Sensing of Neurochemicals -- Modeling protein and oxidative metabolism in Parkinson's disease -- Mathematical Models of Dopamine Metabolism in Parkinson$1 (Bs Disease -- Index.s
Keywords: Life sciences; Neurosciences; Systems biology; Life Sciences; Systems Biology; Neurosciences; Biomedicine general; Electronic books